Assessing mathematics teachers’ knowledge of geometry based on Van Hiele Model of Geometric Thought - E. Reyhani; S.M. Emam jome; B. Saleh Sedghpour; A. Moradi (Fanāvarī-i āmūzish, 2010)
The purpose of this study is to assess the mathematics teachers’ knowledge of geometry based on Van Hiele Model of Geometric Thought. 38 pre-service and 12 in-service mathematics teachers participated in this study. In this research, a test was devised according to Van Hiele Model. T-test with  was deployed in order to analyze data. The research method is causal-comparative method. Finding show that the participants have passed through third level of thinking but have not achieved fourth level of thinking. While researches indicate that teachers should at least acquire the fourth level of thinking. Hence the geometric course in the current program for preparing mathematics teachers, have not offered sufficient professional knowledge for pre-service and in-service mathematics teachers.